A case of swine vesicular disease in Greece - ΔΗΜΗΤΡΙΑΔΗΣ, Ι.; ΠΑΠΠΟΥΣ, Χ.; ΜΠΡΟΒΑΣ, Δ. (Journal of the Hellenic Veterinary Medical Society, 2019)
In July 1979 a very mild contagious disease was observed in pigs showing lameness and ulcerations on feet and mainly in the region of heels without lesions in the mouth or the snout. The disease affected mainly animals 25 days to 5 months old in a herd of 500 pigs in Aspropyrgos Commune (Attica). These animals were fed with waste food. A sample of foot lesions scrapings from ill pigs of the breeding was inoculated in IB RS-2 cell cultures and in 1-2 days newborn mice intraperitoneal!ν. A cytopathic and lethal for mice virus was isolated. Repeated complement fixation tests gave negative results for Foot - and - Mouth Disease. This virus is cytopathic in pig cell lines (IB-RS-2, PKI5) but not in primary cell cultures from calf embryo kidneys. It is resistant to 50°C/60' in presence or not of 1 M MgCl3 ions, to pH values 3-5-9, to ether, chloroform and trypsin treatment. The virus grown on IB-RS-2 cells has been shown to be Swine Vesicular Disease virus by using the complement fixation and serum neutralization tests (Hyperimmune guinea pig serum UKG/27/72 received from Ptrbright). The disease was reproduced by infection of the isolated virus in one pig and in another one in contact with it. High titres of neutralizing antibodies against this virus were detected in sera of convalescent animals. The diagnosis has been confirmed by the Animal Virus Resarch Institute at Pirbright. This is the first case of Swine Vesicular Disease observed in Greece.